1999
DOI: 10.1021/om980913q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Phosphaalkene-Based Bidentate Ligands Mes*PCH(3-R-Ar) (R = Pyridyl, Carbaldimino) and Formation of Three-Membered Palladacycles Mes*(Me)P−CH(3-R-Ar)−PdCl by Carbapalladation of the PC Double Bond

Abstract: Novel functionalized phosphaalkene-based bidentate ligands of the type 1-[(E)-Mes*PC(H)]-3-R-benzene (8, R = N-phenylcarbaldimino; 2, R = 2-pyridyl; Mes* = 2,4,6-tri-tert-butylphenyl) were prepared via a Pd(0)-catalyzed cross-coupling reaction of (Z)-bromophosphaalkene (Z)- 1 with Grignard reagents. The reaction of 8 and 2 with MePdCl(COD) furnished three-membered phosphapalladacycles of the type (9, R = N-phenylcarbaldimino; 10, R = 2-pyridyl), displaying intramolecular coordination between the phosphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…As shown in Scheme b, Bickelhaupt et al . reported that the cross‐coupling reaction using gem‐ dibromophosphaethene 1 was unsuccessful because the palladated intermediate easily generates the phosphanylidenecarbene (phosphaisonitrile) intermediate [Mes*P=C:], affording phosphaalkyne (phosphaethyne) 2 . Nevertheless, reaction conditions for cross‐coupling using 1 warrant investigation and one approach is to prevent the dual elimination of bromides from 1 .…”
Section: Figurementioning
confidence: 99%
“…As shown in Scheme b, Bickelhaupt et al . reported that the cross‐coupling reaction using gem‐ dibromophosphaethene 1 was unsuccessful because the palladated intermediate easily generates the phosphanylidenecarbene (phosphaisonitrile) intermediate [Mes*P=C:], affording phosphaalkyne (phosphaethyne) 2 . Nevertheless, reaction conditions for cross‐coupling using 1 warrant investigation and one approach is to prevent the dual elimination of bromides from 1 .…”
Section: Figurementioning
confidence: 99%
“…Figure 1a shows an STM image obtained for a 1 mm solution of Ir-C 18 on HOPG. The image shows several crystalline domains with dimensions of tens of nanometers.…”
Section: Resultsmentioning
confidence: 99%
“…Our attempts to obtain an STM image afforded only diffuse unclear images. We believe that this is due to a more disordered, and hence more mobile, molecular arrangement as im- On the basis of the above observations, we have concluded that the molecular arrangement in the two-dimensional domains from the optically active Ir-C 18 is different from that of racemic Ir-C 18 . This in turn leads to the conclusion that the nano-and microslips prepared from the racemic mixture of Ir-C 18 are racemates.…”
mentioning
confidence: 81%
See 2 more Smart Citations